Nauczyciele języków obcych: Iluzje – fakty – badania - Komorowska, Hanna (Neofilolog, 2023)
The article aims to analyze meanings underlying the popular concepts of a good teacher, efficient teacher, novice, expert and experienced non-expert from a diachronic perspective. Criteria used across developmental stages of second language acquisition/ foreign language teaching in the process of teacher accreditation are examined, as well as social contexts influencing teacher evaluation. Reasons for teachers’ dissatisfaction with European school systems are presented, as well as coping strategies employed by frustrated teachers. New challenges springing from economic, social and cultural student diversity are also discussed. Implications are sought for pre- and in-service teacher education.